Prehistoric Puebloan yucca (Yucca) quids with wild tobacco (Nicotiana) contents: Molecular and morphological evidence from Antelope Cave, northwestern Arizona. (June 2015) - Adams, Karen R.; Johnson, Keith L.; Murphy, Terence M.
<x content-type="archive" xml:space="preserve">Abstract</x> Unburned yucca (Yucca) quids with wild tobacco (Nicotiana) contents have been preserved within Antelope Cave in northwestern Arizona. Although the cave was visited during the Archaic, Southern Paiute, and Euro-American periods, material culture remains and radiocarbon dates indicate the heaviest use by the Virgin Anasazi (a.d. 1–1000). Quids are wads of fiber twisted or knotted into a ball for insertion into the mouth. Ten of the quids examined were clearly made from the fibers of Yucca plants, based on 6–7 base pairs identified via analysis of DNA sequences near the trnL gene of chloroplastic DNA. Twenty-seven of thirty quids examined were wrapped around a range of wild tobacco (Nicotiana) plant parts (e.g., capsule, seed, calyx, pedicel, main stem, leaf). Quids have been interpreted as serving various needs (food, ceremonial/ritual, other). The inclusion of tobacco and the diverse recovery contexts suggest the Antelope Cave quids provided occupants with a personal stimulant experience.